2012
DOI: 10.1002/bdra.23048
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Lyar and p53 are synergistically lethal in female mice

Abstract: Lyar/p53 mutant mice represent a new digenic model of NTDs. Furthermore, these studies identify Lyar as a novel candidate gene for a role in human NTDs. These results provide new data to support the idea that loss of a p53-mediated developmental checkpoint may increase the risk of NTDs owing to some germline mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(59 reference statements)
2
11
0
Order By: Relevance
“…During the preparation of our manuscript, another study on Lyar-mutant mice generated by gene-trap insertion was reported (Wang et al, 2012). Similar phenotypes were observed in the mice with reduced LYAR expression, in that the mutant mice were viable and fertile.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…During the preparation of our manuscript, another study on Lyar-mutant mice generated by gene-trap insertion was reported (Wang et al, 2012). Similar phenotypes were observed in the mice with reduced LYAR expression, in that the mutant mice were viable and fertile.…”
Section: Discussionsupporting
confidence: 61%
“…Similar phenotypes were observed in the mice with reduced LYAR expression, in that the mutant mice were viable and fertile. Further genetic analyses showed that Lyar and p53 double-mutant female mice exhibited embryonic lethality, suggesting that there is a genetic interaction between the two genes during embryogenesis (Wang et al, 2012). Thus, it is possible that the alterations in molecular or cellular processes caused by Lyar deficiency could be limited by p53 or a p53-like factor during spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…4); thus, it is unlikely that LYAR regulates ribosome biogenesis via increased c-Myc expression or affecting c-Myc function. Recently, functional relationship between the tumor suppressor p53 and Lyar was shown using the knockout mice of these genes (Wang et al 2012). p53 is activated by perturbation of ribosome biogenesis and leads to cell-cycle arrest and apoptosis as reported in animal models of Treacher-Collins syndrome (TCS) that is a congenital disorder of craniofacial development arising from mutations in the TCOF1 gene (Jones et al 2008;Fumagalli & Thomas 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The sex-specific effect of p53 loss on neural tube closure has been ascribed to differences in X gene dosage [ 70 ]. In addition, the zinc finger protein, Lyar, has been shown to function synergistically with p53 loss in promoting NTDs and death of female embryos [ 71 ].…”
Section: Mechanisms Of Sex Effects In Cancermentioning
confidence: 99%